(untitled) (Research, Society and Development, 2021)
Objective: This study aims to establish the anatomical relationship between the mandibular canal and the third molars, based on analysis by Cone Beam Computed Tomography. Methodology: Computed Tomography analysis of 67 third molars was performed using Blue Sky Plan 4 virtual planning software. The anatomical dispositions of the third molars and mandibular canal were evaluated, as well as the factors that favor the contact between these structures. Result: There was a prevalence of 76.1% for biradicular third molars, 52.2% for class 1 and 71.6% class A. Vertical and mesioangulated teeth had a higher prevalence, with 38.8% and 35.8% respectively. Sicher and Tandler’s classification presented 41.8% of the canals as type I, while in the buccal-lingual positioning, 89.5% of the canals were located through the buccal. 44.8% of the teeth had contact with the canal and the factors with statistical significance were: female gender (p = 0.019), number of roots (p = 0.019), class 3 (p = 0.004) and C (p = 0.012) teeth and lingual positioning of the mandibular canal (p = 0.016). About the anatomical delimitations, the mean diameter of the canal was 3.14 mm and the distances related to the dental roots, lingual, buccal and inferior cortical bony were 2.77, 3.53, 4.56 and 8.32 milimeters, respectively. Conclusion: Therefore, the assessment of third molars by computed tomography is essential during preoperative planning, as it identifies anatomical relationships that favor contact between the tooth and the mandibular canal and helps to reduce the incidence of sensorineural disorders.